Effect of Cinnamaldehyde From Cinnamomum (Cinnamomum burmanni Ness ex Bi.) as an Encapsulation Agent Of Lemuru Fish Oil on In Vitro Gas and Methane Production - Wibowo, Siti 'Athiya; Yusiati, Lies Mira; Hanim, Chusnul; Bachrudin, Zaenal; Widyobroto, Budi Prasetyo (Faculty of Animal Science, Universitas Gadjah Mada, 2024)
Polyunsaturated fatty acids (PUFA) supplementation in animal feed is expected to increase unsaturated fatty acids content in livestock products. Lemuru fish oil supplementation as a source of PUFA can function as a hydrogen sink to reduce methane production. The contribution of methane gas emissions in livestock reaches 15-17% of the world's methane gas emissions. Encapsulation of PUFA using natural ingredients of cinamaldehyde is expected to be a solution to increasing PUFA in livestock product and improving environmentally friendly animal husbandry. This study aimed to determine the effect of using cinnamaldehyde as an encapsulation agent for lemuru fish oil as a source of PUFA on in vitro gas, methane and CO2 productions. Treatments consisted of different levels of cinnamaldehyde, namely 0, 250, 500, 750 and 1000 (mg/kg feed DM), with the 5% lemuru oil as PUFA source. The experimental design used a one-way ANOVA in completely randomized design pattern consisting of five treatments and three replicates. Each replicate was duplicate, and then, if there were significant differences, it was continued with Duncan's New Multiple Range Test (DMRT) with SPSS version 23. This study discovered that the use of cinnamaldehyde did not affect the in vitro kinetics of gas and CO2 production. The use of cinnamaldehyde level of 500 mg/kg DM feed is the optimal level that can be used as an encapsulation agent for lemuru oil without causing an increase in methane production.